Evaluating design features to support inclusive, self-directed, and active healthy living behaviours - Tracada, Eleni; Sorensen Allacci, MaryAnn (Frontiers in Built Environment, 2023)
Active healthy living design has typically focused on urban and community environments to support physical activity; this article looks at an expanded definition of active healthy living opportunities at building level design for various groups. We wanted to engage youth, adults, and diversely abled people through a form of inclusive design that encourages individuals to venture out of their private homes, workplaces, or other isolating conditions and explore areas of shared spaces or get outside of personal environments and buildings for self-directed, restorative activity. Incentives for people to venture outside of private spaces became even more important for maintaining healthy minds and bodies during the recent pandemic. The objectives of this discussion are to propose a multidisciplinary tool to facilitate decisions around creating shared spaces in different building typologies that promote active, self-directed behaviour by occupants to engage physically, socially, or psychologically with features that support health and well-being. We first examined a wide range of theories and design practices for potential applications to building-centred design that supports healthy behaviour, reduces environment stress, and employs space syntax and the Biophilic Healing Index to help encourage healthy behaviours by a wide range of occupant ages and abilities in and around buildings. A rating scale was then associated with criteria representing evidence-based guidelines, and capable of being fitted for use as a teaching-learning and discussion aid. An overview of data from demonstration of the tool is presented, along with feedback on proposed improvements and how these might impact professional practice.